ETHNOBOTANY, CHEMISTRY AND PHARMACOLOGY OF AN AROMATIC GENUS ANISOMELES LINN. IN INDIA: Life Sciences-Natural Chemistry - K. SRI RAMA MURTHY; M. CHANDRASEKHARA REDDY; T.PULLAIAH (International Journal of Life Science and Pharma Research, 2022)
Anisomeles is an aromatic genus that belongs to the family Lamiaceae. The members of this genus are characterized by the presence of camphor-scented flowers. Members of this genus are widely used in folklore medicine in countries like India to cure various diseases like fever, anti- inflammatory, antiseptic, skin diseases, abdominal pain, psoriasis etc. In the present review traditional uses, phytochemistry and pharmacology of members belongings to this genus are presented. A wide range of chemical constituents were isolated from different species of Anisomeles. Among all the constituents that were isolated from these species anisomelic acid and ovatodiolids are the more abundant bioactive compounds, which show greater biological significance. They show a wide range antimicrobial, antipyretic, anti-inflammatory, antioxidant, cytoprotective, anticancer, insecticidal, and herbicidal properties. These species have strong cytotoxicity and anticancer properties which should be further evaluated. The literature presented in this review will provide a platform for further research on this genus to develop new safe plant based drugs to cure cancer.